Establishment and growth responses of Nile tilapia embryonic stem‐like cell lines under feeder‐free condition. (23rd February 2017) - Fan, Zhenhua; Liu, Linyan; Huang, Xiaohuan; Zhao, Yang; Zhou, Linyan; Wang, Deshou; Wei, Jing
Abstract : Embryonic stem (ES) cells provide an invaluable tool for molecular analysis of vertebrate development and a bridge linking genomic manipulations in vitro and functional analysis of target genes in vivo . Work towards fish ES cells so far has focused on zebrafish ( Danio renio ) and medaka ( Oryzias latipes ). Here we describe the derivation, pluripotency, differentiation and growth responses of ES cell lines from Nile tilapia ( Oreochromis niloticus ), a world‐wide commercial farmed fish. These cell lines, designated as TES1‐3, were initiated from blastomeres of Nile tilapia middle blastula embryos (MBE). One representative line, TES1, showed stable growth and phenotypic characteristics of ES cells over 200 days of culture with more than 59 passages under feeder‐free conditions. They exhibited high alkaline phosphatase activity and expression of pluripotency genes including pou5f3 (the pou5f1/oct4 homologue), sox2, myc and klf4 . In suspension culture together with retinoic acid treatment, TES1 cells formed embryoid bodies, which exhibited expression profile of differentiation genes characteristics of all three germ cell layers. Notably, PKH26‐labeled TES1 cells introduced into Nile tilapia MBE could contribute to body compartment development and led to hatched chimera formation with an efficacy of 13%. These results suggest that TES1 cells have pluripotency and differentiation potential in vitro and in vivo . In the conditioned DMEM, all of the supplements including the fetal bovine serum, fish embryonic extract, fish serum, basic fibroblast growth factor and non‐protein supplement combination 5N were mitogenic for TES1 cell growth. This study will promote ES‐based biotechnology in commercial fish. Abstract : Nile tilapia ES‐like cell line (TES1) has been successfully developed under feeder‐free culture condition, which retains stable growth for over 200 days with more than 59 passages. TES1 cells have pluripotency and differentiation potential in vitro and in vivo.